A particle-in-cell method for anisotropic fluid simulation - Perreiras, Emanuel Antônio; Vieira, Marcelo Bernardes; Machado, Arthur Gonze; Renhe, Marcelo Caniato; Giraldi, Gilson Antônio (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI), 2021)
This work presents a method for conforming fluid flow to tensor fields in particle-in-cell simulations. Our focus is on the use of tensor fields as a medium to deflect fluids for computer graphics applications. The anisotropic fluid simulation here presented adapts the Fluid-Implicit-Particle (FLIP) method, by including the tensor field information in the advection and projection steps. Numerical solutions are proposed for adapting the anisotropic advection to the particle-in-cell model and for solving the anisotropic Helmholtz projection for Marker-and-Cell (MAC) grids. Suitable boundary conditions are also provided to ensure proper anisotropic fluid behavior. To evidence the capabilities of this approach, we present simulations with different tensor fields composed of isotropic, linear, and planar tensors. Experimental results show that our method is capable of deflecting or withholding flow in specific directions, according to the characteristics of the underlying tensor field, producing visual outcomes typically encountered in anisotropic media, such as permeable-like effects.